Cerebral small vessel disease is associated with dysregulation in the ubiquitin proteasome system and other major cellular pathways in specific brain regions - Ritz, Marie-Françoise; Grond-Ginsbach, Caspar; Kloss, Manja (Neurodegenerative diseases, 2017)
Background/Aims: Cerebral small vessel disease (SVD) is characterized by periventricular white matter (WM) changes and can lead to vascular dementia, the second most common form of age-dependent dementia. The pathogenesis of the disease remains poorly understood, and studies of its molecular basis are limited. By profiling gene expression of dissected postmortem brain tissue in SVD patients and comparisons with tissue of nonneurological controls, we aimed to identify genes and processes that are involved in the pathogenesis of SVD to gain new pathogenetic insights. Methods: We performed genome-wide expression analyses in postmortem brain tissue samples dissected from frontal, temporal, and occipital lobes as well as basal nuclei comprising thalamus, basal ganglia, and hippocampus from 5 SVD cases and 5 nonaffected control cases. Cellular pathways associated with differently expressed genes were identified in each brain region individually. Results: This analysis disclosed regional differences, with frontal lobe and thalamus showing the highest numbers of genes with significantly altered expression. Biological functions and pathways associated with changed gene expression depicted brain area-specific defective pathways. Vessel-associated functions, such as increased extracellular matrix-receptor interactions and cell adhesion molecules, were enhanced in all regions. Inflammation and apoptosis were induced particularly in basal nuclei and temporal and occipital regions. Interestingly, genes associated with the ubiquitin-dependent proteolysis (ubiquitin proteasome system) pathway were downregulated in the frontal lobe and in the thalamus, leading to the formation of protein aggregates. Conclusion: This analysis deciphers brain region-specific molecular processes to increase the present knowledge of SVD pathology and determine new potential therapeutic targets.